Vulnerabilities in Water Distribution Systems Using N-k Contingency Analysis - Zhou, Xiangnan; Duenas-Osorio, Leonardo; ICASP14 (My University, 2023)
Adequate performance of water distribution systems is at the core of community resilience. Water distribution systems are vulnerable to a variety of hazards, as they are susceptible to direct physical damage (e.g., earthquakes, winter storms, floods, and deterioration), and to service interruptions from failures of critical infrastructure they depend on (e.g., power and telecommunication systems). In this study, we adapt the contingency analysis, which is widely used to study power system security, to assess the vulnerability of water distribution systems. Multi-stage contingency analyses support resilience analysis: first by sampling possible system failure scenarios conditional to component failures, independent of the hazard; second by evaluating system functionality loss (e.g., water service availability loss) under failure scenarios through physics-based models; and third by identifying critical failure scenarios that cause significant functionality loss and ranking the criticality of corresponding components for future intervention. We demonstrate our approach on two cases, one synthetic with Net3 in the Water Network Tool for Resilience (WNTR), and one practical with the water distribution system of the City of Lumberton, NC, which is a community testbed on the Interdependent Networked Community Resilience Modeling Environment (IN-CORE). The contingency analysis of these cases reveals different vulnerability patterns mediated by network layout and operation settings. In particular, the Net3ﾒs most vulnerable locations are where its backbone distribution lines lay because it is not feasible to shift their flow loads to adjacent assets due to capacity limitations. The most vulnerable area of the Lumberton network is where large, concentrated demands co-exist with sparse distribution lines that limit alternative flow paths. Overall, vulnerable areas relate to a lack of global and local connectivity redundancy, and local flexibility in system flow routing. Our approach can reveal intrinsic system vulnerabilities relevant to any hazard events. It complements existing hazard-dependent resilience analyses to support decisions and help community stakeholders allocate limited resources to improve the future resilience of their water distribution systems.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED